Enhanced Air–Sea Exchange of Heat and Carbon Dioxide Over a High Arctic Fjord During Unstable Very-Close-to-Neutral Conditions - Andersson, Andreas; Sjöblom, A.; Sahlée, E.; Falck, E.; Rutgersson, A. (Boundary-Layer Meteorology, 2019)
Eddy-covariance measurements made in the marine atmospheric boundary layer above a high Arctic fjord (Adventfjorden, Svalbard) are analyzed. When conditions are unstable, but close to neutral −0.1 < z/L < 0, where z is the height, and L is the Obukhov length, the exchange coefficient for sensible heat CH is significantly enhanced compared with that expected from classical surface-layer theory. Cospectra of the vertical velocity component (w) and temperature (T) reveal that a high-frequency peak develops at f ≈ 1 Hz for z/L > − 0.15. A quadrant analysis reveals that the contribution from downdrafts to the vertical heat flux increases as conditions become close to neutral. These findings are the signature of the evolving unstable very-close-to-neutral (UVCN) regime previously shown to enhance the magnitude of sensible and latent heat fluxes in the marine surface layer over the Baltic Sea. Our data reveal the significance of the UVCN regime for the vertical flux of the carbon dioxide (CO2) concentration (C). The cospectrum of w and C clearly shows how the high-frequency peak grows in magnitude for z/L > − 0.15, while the high-frequency peak dominates for z/L > − 0.02. As found for the heat flux, the quadrant analysis of the CO2 flux shows a connection between the additional small-scale turbulence and downdrafts from above. In contrast to the vertical fluxes of sensible and latent heat, which are primarily enhanced by the very different properties of the air from aloft (colder and drier) during UVCN conditions, the increase in the air–sea transfer of CO2 is possibly a result of the additional small-scale turbulence causing an increase in the water-side turbulence. The data indicate an increase in the gas-transfer velocity for CO2 for z/L > − 0.15 but with a large scatter. During the nearly 2 months of continuous measurements (March–April 2013), as much as 36% of all data are associated with the stability range −0.15 < z/L < 0, suggesting that the UVCN regime is of significance in the ...